Association of family function and suicide risk in teenagers with a history of self-harm behaviors: mediating role of subjective wellbeing and depression - Chen, Mo; Zhou, Yang; Luo, Dan; Yan, Shu; Liu, Min; Wang, Meng; Li, Xin; Yang, Bing Xiang; Li, Yi; Liu, Lian Zhong (Frontiers in Public Health, 2023)
Background: A history of self-harm behaviors is closely associated with subsequent suicide death. Although many factors associated with suicide have been identified, it remains unclear how these factors interact to influence suicide risk, especially among teenagers with a history of self-harm behaviors. Methods: Data was collected from 913 teenagers with a history of self-harm behaviors through a cross-sectional study. The Family Adaptation, Partnership, Growth, Affection and Resolve index was used to assess teenagers’ family function. The Patient Health Questionnaire-9 and the Generalized Anxiety Disorder-7 were used to evaluate depression and anxiety in teenagers and their parents, respectively. Delighted Terrible Faces Scale was used to assess teenagers’ perception of subjective well-being. The Suicidal Behaviors Questionnaire-Revised was used to evaluate teenagers’ suicide risk. Student’s t-test, one-way ANOVA, multivariate liner regression, Pearson’s correlation and a structural equation model (SEM) were applied in data analysis. Results: Overall, 78.6% of teenagers with a history of self-harm behaviors were at risk for possible suicide. Female gender, severity of teenagers’ depression, family function and subjective well-being were significantly associated with suicide risk. Results of SEM suggested that there was significant chain mediation effect of subjective well-being and depression between family function and suicide risk. Conclusions: Family function was closely associated with suicide risk in teenagers with a history of self-harm behaviors, and depression and subjective well-being were sequential mediators in the association between family function and suicide risk.